Emotion Recognition Biases in Alcohol Use Disorder. (5th July 2018) - Freeman, Clara R.; Wiers, Corinde E.; Sloan, Matthew E.; Zehra, Amna; Ramirez, Veronica; Wang, Gene‐Jack; Volkow, Nora D.
Abstract : Background: Alcohol use disorder (AUD) has been associated with impairments in cognitive and emotional function, including difficulty identifying emotional facial expressions. However, it is unclear whether these deficits are associated with alcohol consumption or related anxious and depressive symptoms. Methods: We compared the recognition of emotional faces expressing happiness, surprise, sadness, fear, anger, and disgust in 19 AUD participants and 19 healthy volunteers using the Cambridge Neuropsychological Test Automated Battery Emotion Recognition Task. We analyzed group differences in response latency, accuracy, and misidentification patterns (as defined by the tendency to mislabel facial expressions as exhibiting specific emotions). To assess whether misidentification patterns were associated with drinking severity, we also examined associations with alcohol consumption over the past 90 days. Results: There were no differences in response latency or accuracy between groups. However, there were group differences in misidentification patterns. While controls tended to misidentify emotional expressions as happy, those with AUD tended to misidentify expressions as angry or disgusted. In AUD participants, the degree to which individuals were biased toward anger or disgust was positively correlated with the number of drinks they consumed in the past 90 days but was not associated with depression or anxiety scores. Conclusions: Our findings suggest that individuals with AUD have a bias toward misidentifying emotional facial expressions as hostile, which is not mediated by associated mood changes. This provides further evidence of disrupted social cognition in AUD. Abstract : Individuals with alcohol use disorder were more likely to misidentify ambiguous emotional facial expressions as displaying anger and disgust as compared to healthy controls. In individuals with alcohol use disorder, these disgust and anger biases correlated positively with alcohol consumption over the past 90 days. Our results provide evidence of altered social cognition in individuals with alcohol use disorder.